Designing an AI-Assisted Pedagogical Model for Arabic Language and Literature Education - Riski Gunawan (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2026)
Artificial Intelligence (AI) has increasingly been integrated into language education, creating new opportunities for personalized learning, adaptive instruction, and interactive educational experiences. However, most existing studies primarily examine AI from a technological perspective, emphasizing its effectiveness in improving linguistic competencies such as vocabulary acquisition, grammar instruction, pronunciation, and writing skills. Comparatively limited attention has been given to the pedagogical design of AI-assisted Arabic language instruction that promotes multicultural competence and religious tolerance, particularly within Indonesian Islamic educational institutions. This conceptual paper aims to develop an AI-assisted pedagogical model for Arabic language education by integrating educational theories, multicultural education, intercultural communicative competence, and responsible AI-supported teaching practices. Drawing upon Constructivism, Social Constructivism, Self-Regulated Learning, Multicultural Education, Intercultural Communicative Competence, and the Technological Pedagogical Content Knowledge (TPACK) framework, the proposed model positions teachers as instructional designers and AI as a pedagogical support tool rather than an instructional substitute. The article argues that meaningful educational outcomes are achieved not through AI itself but through carefully designed learning activities that encourage inquiry, dialogue, collaboration, reflection, and authentic communication. These pedagogical processes subsequently facilitate the development of multicultural competence and religious tolerance while simultaneously strengthening Arabic language proficiency. The proposed model contributes to Arabic language education by offering a pedagogically grounded framework that assists educators in integrating AI responsibly within Indonesian Islamic schools. It also provides a conceptual foundation for future empirical research examining the effectiveness of AI-assisted pedagogy in promoting both linguistic and character development.